Evaluation of 2,6-xylidine precipitate on sealer penetration of calcium silicate-based sealer and resin-based sealer: An in vitro study - M. B. Kalpana; Divya Shetty; Rajaram Naik (Endodontology)
Aim: To evaluate and compare the effect of 2,6-xylidine precipitate on sealer penetration of calcium silicate-based sealer and epoxy resin-based sealer. Methods: Forty-eight single-rooted premolar teeth were selected and were decoronated to root length of 14 mm. The samples were primarily allocated into two groups according to the sealer (n = 24): Group A = BioRoot RCS and Group B = AH Plus; further, each group was subdivided into two subgroups based on the test solutions employed (n = 12): Group A1, B1 – Irrigation with 2.5% NaOCl and Group A2, B2 – Intrapulpal injection with 2% lidocaine hydrochloride (LA) followed by irrigation with 2.5% NaOCl. Following that, all samples underwent instrumentation utilizing the ProTaper Universal rotary system up to the F3 file size, followed by obturation using appropriate sealers and gutta-percha. Sections were taken 3 mm from the apex, and sealer penetration was assessed using confocal laser scanning microscope for quantitative variables. Results: Group A1 exhibited greater sealer penetration compared to other groups, whereas Group B2, which contained precipitate, showed the least sealer penetration, with statistical significance at P < 0.05. The descending order of sealer penetration was observed as follows: A1 > A2 > B1 > B2. Conclusion: Within the limits of the study, it was concluded that sealer penetration of both the sealers was influenced by 2,6-xylidine precipitate.